Three dimensional structure prediction of recombinant endochitinase from trichoderma virens UKM-1 - Nadiawati, Alias; Nor Muhammad, Mahadi; Abdul Munir, Abdul Murad; Farah Diba, Abu Bakar (2011)
Chitinases (EC 3.2.11.14) are capable of hydrolyzing chitins by splitting their ß-1,4-glucosidic bonds. They are present in a wide range of organisms including the fungus Trichoderma virens UKM-1. A gene encoding endochitinase from Trichoderma virens UKM-1 had successfully been cloned (with GenBank Accession number DQ 865246) and expressed in Escherichia coli BL21 (DE3). As a member of glycosyl hydrolases, chitinases are assumed to have a similar catalytic mechanism and structure as other enzymes such as lysozyme. A predicted three dimensional (3D) structure of endochitinase derived from Trichoderma virens UKM-1 was successfully constructed using the Swiss-Prot model server and analyzed by PyMOL software. The prediction of the structure was done by comparing T. virens UKM-1 endochitinase with seven published 3D structures of chitinases from the Swiss-Prot database. Recombinant endochitinase from T. virens UKM-1 was shown to have a TIM-barrel structure with eight parallel ß-sheets and eight α-helices laid down in the inner barrel together with three-stranded ß-sheets. These characteristics revealed the aspects of the catalytic centers of family 18 chitinases. An extensive study was done on the multiple sequence alignment of various class V, family 18 chitinases by using DNASIS Software. Two conserved consensus motif boxes SxGG (Box 1) and DxxDxDxE (Box 2) were found at the N-terminal amino acid sequence of endochitinase from T. virens UKM-1 which were involved in catalysis.